Sustainable business in the Arab Region : corporate social responsibility vs culture - Diab-Bahman, Randa (Emerald points., 2024)
Existing research on corporate social responsibility (CSR) is written from a largely Westernized viewpoint, but what is the relationship between CSR, organizational - and wider - culture on the sustainability of businesses in the Arab region? Also, what impact do Islamic beliefs and values have on ethical business practices? Randa Diab-Bahman explores the understanding and expression of CSR in an Arab context; through a qualitative pilot study with prominent CSR experts (people with leading roles in CSR in the private, public and non-profit sector) in a predominately Islamic setting. Sustainable Business in the Arab Region confirms the importance of cultural elements in influencing the understanding and expression of CSR. Interestingly, the importance of the Islamic religion and specific aspects of its religious doctrine are found to be particularly important to understanding why CSR may be expressed differently in an Arab context. The implications of these findings are important for policymakers, as it can help them better align their CSR initiatives and better understand their possible impact on stakeholders. Not only relevant to those researching CSR across different organizational cultures, the findings here are important to anyone doing sustainable business globally.